Bullwhip Effect Variance Ratio Approximations for Aggregated Retail Orders in Supply Chains - Akram Amine El-Tannir (International Journal of Supply Chain Management, 2014)
This paper develops two approximations to estimate the variance of aggregated retailer orders that is a form of the widely recognized Bullwhip effect, using the renewal theory and available Markov chain models for the two-echelon supply chain. These approximations are used to develop several managerial insights on inventory policies used by retailers who make replenishment orders to a supplier that uses a periodic review inventory policy where market demand is assumed to be based on Poisson market orders.